Tea tree oil: contact allergy and chemical composition - de Groot, Anton C.; Schmidt, Erich (Contact dermatitis, 2016)
Summary In this article, contact allergy to, and the chemical composition of, tea tree oil (TTO) are reviewed. This essential oil is a popular remedy for many skin diseases, and may be used as neat oil or be present in cosmetics, topical pharmaceuticals and household products. Of all essential oils, TTO has caused most (published) allergic reactions since the first cases were reported in 1991. In routine testing, prevalences of positive patch test reactions have ranged from 0.1% to 3.5%. Nearly 100 allergic patients have been described in case reports and case series. The major constituents of commercial TTO are terpinen‐4‐ol, γ‐terpinene, 1,8‐cineole, α‐terpinene, α‐terpineol, p‐cymene, and α‐pinene. Fresh TTO is a weak to moderate sensitizer, but oxidation increases its allergenic potency. The major sensitizers appear to be ascaridole, terpinolene, α‐terpinene, 1,2,4‐trihydroxymenthane, α‐phellandrene, and limonene. The clinical picture of allergic contact dermatitis caused by TTO depends on the products used. Most reactions are caused by the application of pure oil; cosmetics are the culprits in a minority of cases. Patch testing may be performed with 5% oxidized TTO. Co‐reactivity to turpentine oil is frequent, and there is an overrepresentation of reactions to fragrance mix I, Myroxylon pereirae, colophonium, and other essential oils.